Impact of budget deficit, quality of governance and financial integrity on economic growth: welfare and non-welfare countries / Kazi Musa - Musa, Kazi (2022)
Government intervention is imperative in the market economic system due to market failures, imperfection, pure public goods, and economic externalities. The impact of budget deficit on economic growth is a puzzle in empirical and seminal literature. Since budget deficit is crucial for the role of welfare and non-welfare countries, there is a considerable research gap on how the budget deficit fund affects economic growth in these countries. This study examines the direct impact of budget deficit on economic growth, splitting the sample into welfare and non-welfare countries. Since the presence of quality of governance (QoG) and financial integrity (FI) in the literature casts doubt on the relationship between budget deficit and economic growth. Therefore, we consider examining the direct impact of QoG and FI on economic growth and the moderating role on the nexus between budget deficit and economic growth to see the impacts in welfare and non-welfare countries. The study data are highly heterogeneous panel data from 1990 to 2020. Therefore, we apply a newly developed econometric model called panel Quantile Regression via Moment Conditions, considering the quantile both in scale and location. Our empirical investigation shows that the budget deficit promotes economic growth in overall sample countries. The comparative analysis confirms that budget deficit promotes economic growth for welfare countries while it impends for non-welfare countries. QoG augments economic growth in different economic circumstances in all samples, while it plays a supportive moderating role for non-welfare and combined sample. The FI has growth-enhancing effects in welfare countries, while insignificantly fluctuating effects for the non-welfare and combined sample and has mostly insignificant oscillating moderating roles. Therefore, the study recommends that welfare countries pursue budget deficits, while non-welfare countries should exercise caution until they have substantial QoG. QoG is also very significant for non-welfare countries as well as for other samples, but excessively tight regulations and rules of QoG and FI frequently slow down economic growth, which policymakers should take into account when formulating policies on budget deficit, QoG, and financial integrity.